Estimating overidentified, nonrecursive, time-varying coefficients structural vector autoregressions - Fabio Canova; Fernando J. Pérez Forero (Quantitative Economics, 2015)
This paper provides a general procedure to estimate structural vector autoregressions. The algorithm can be used in constant or time-varying coefficient models, and in the latter case, the law of motion of the coefficients can be linear or nonlinear. It can deal in a unified way with just-identified (recursive or nonrecursive) or overidentified systems where identification restrictions are of linear or of nonlinear form. We study the transmission of monetary policy shocks in models with time-varying and time-invariant parameters.
Keywords: 330; Time-varying coefficient structural VAR models; Metropolis algorithm; identification restrictions; monetary transmission mechanism